The atypical startup characteristics of a pump as turbine - Yu‐Liang Zhang; Yan‐Juan Zhao (Energy Science & Engineering, 2022)
Abstract A generalized Euler equation of pump as turbine is derived, and the transient hydraulic performance of a centrifugal pump as turbine during an atypical startup period is measured. Meanwhile, the dimensionless analysis and the additional theoretical head calculation are also conducted. It is found that the transient characteristics of pump as turbine during atypical startup period mainly come from the rotational acceleration effect, rather than the flow inertia effect. The final stable values of dimensionless flowrate coefficient and dimensionless head coefficient are both closely related to the steady rotating speed and flowrate after startup process, but the dimensionless power coefficient is not remarkably related to them. In an atypical startup, the impact phenomena occur in both flowrate curve and outlet static pressure curve. At the same steady rotating speed, the larger the steady flowrate is, the more serious the flowrate impact is. Under the same steady flowrate, the lower the steady rotating speed is, the more remarkable the static pressure impact at the outlet is.